Efeito de épocas-níveis de desfolha do milho sobre a produtividade do consórcio milho-feijão: II. Cultura do feijão - Silva Araújo, Dorival; Domingos Galvão, José; Nogueira Fontes, Luiz Antônio; Cardoso, Antônio Américo (Revista Ceres, 2025)
The effects of 5 defoliation times on 2 maize cultivars in 2 planting densities (25 and 50 thousand/ha), were studied on dry bean in a maize-dry bean mixed crop. Maize hybrids AG-351 (low growth habit) and AG-259 (tall growth habit) were used. Bean cultivar ‘Negrito 897' was used in densities of 160 and 260 thousand/ha.